1992
DOI: 10.1002/jnr.490320312
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced permeabilities of cationized‐bovine serum albumins at the blood‐nerve and blood‐brain barriers in awake rats

Abstract: Permeability-surface area products (PAs) of the blood-nerve barrier (BNB) and blood-brain barrier (BBB) to 125I-labeled native bovine serum albumin (nBSA, pI approximately 4), and to 2 cationized albumins (cBSA) of differing pI (pI approximately 8 and 11), were quantitatively determined in awake rats, using an i.v. bolus injection technique. Mean PAs of the BNB and BBB to 125I-nBSA, after a circulation time of up to 120 min, were (0.17 +/- 0.23) and (0.09 +/- 0.05) x 10(-5) ml/s.g. wet wt, respectively (n = 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1994
1994
2003
2003

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…The effect of protein surface charge on the transcellular protein flux rate across endothelial cells (Smith & Borchardt, 1989), hepatocytes (Wall & Maack, 1985) and proximal tubular cells (Park & Maack, 1984) is well documented, as is its role in capillary permeability (Michel et al , 1985). Ghitescu et al (1992) and Wadhwani et al (1992) showed that protein surface charge is an important factor determining the membrane protein permeability properties. Charged groups at the membrane surface also have been shown to affect the activity of membrane‐bound enzymes by altering the local substrate and/or product concentration (Wojtczak et al , 1988).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of protein surface charge on the transcellular protein flux rate across endothelial cells (Smith & Borchardt, 1989), hepatocytes (Wall & Maack, 1985) and proximal tubular cells (Park & Maack, 1984) is well documented, as is its role in capillary permeability (Michel et al , 1985). Ghitescu et al (1992) and Wadhwani et al (1992) showed that protein surface charge is an important factor determining the membrane protein permeability properties. Charged groups at the membrane surface also have been shown to affect the activity of membrane‐bound enzymes by altering the local substrate and/or product concentration (Wojtczak et al , 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Given the number of publications describing ionic interactions between cellular substrates and cell membranes, protein surface charge (pI) may be an important factor to consider when studying uptake processes. For example, cell membrane surface charge is known to affect the activity of membrane‐bound enzymes, protein‐membrane adsorption properties, transmembrane flux and capillary permeability properties of proteins (Norde & Lyklema, 1978; Park & Maack, 1984; Michel et al , 1985; Wojtczak et al , 1988; Smith & Borchardt, 1989; Ghitescu et al , 1992; Nishida et al , 1992; Wadhwani et al , 1992). Similarly, the surface charge of proteins affects their membrane adsorptive properties (Norde & Lyklema, 1978; Nishida et al , 1992).…”
Section: Introductionmentioning
confidence: 99%
“…A typical example is the use of cationized proteins in brain delivery. It has been demonstrated that cationized albumin is able to traverse the capillary walls of isolated bovine brain capillaries [Kumagai et al, 1987] and penetrate the brain of the awake rat [Wadhwani et al, 1992].…”
Section: Drug Targetingmentioning
confidence: 99%
“…Proteins such as albumin have been chemically modified to make them strongly basic ("cationized") or to give them additional carbohydrate groups ("glycated"). These modified proteins bind to and are transported across the otherwise impermeable endothelium Wadhwani et al, 1992). Some natural plasma proteins, notably transferrin (Pardridge et al, 1992;Rosenthal and Soothill, 1962) and insulin , enter the brain by receptor-mediated transport across endothelial cells.…”
Section: The Blood-brain and Blood-cerebrospinal Fluid Barriersmentioning
confidence: 99%